2019
DOI: 10.3350/cmh.2019.0015
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia: Ammonia metabolism and hepatic encephalopathy

Abstract: Sarcopenia includes loss of muscle mass and/or strength leading of physical derangements and frailty. 1,2 Presence of cirrhosis is an important risk factor for the development of sarcopenia as a result of metabolic derangements caused by hepatocyte dysfunction. Sarcopenia is a major complication in cirrhosis and almost 50 to 70% of them develops sarcopenia. 3 The prevalence rates are much higher in males (50-70%) in comparison to female cirrhosis (≤20%). 4 The severity and prevalence of sarcopenia in cirrhosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 93 publications
1
61
0
1
Order By: Relevance
“…The degree of sarcopenia was associated with Child-Pugh score in patients with cirrhosis, and sarcopenia was a predictor of survival independently or in combination with the model for end-stage liver disease (MELD) score, especially in patients with low scores (<15) [ 109 , 111 , 114 ]. Unfortunately, after liver transplantation, sarcopenia did not improve and even worsened because of immunosuppressive drugs such as steroids, calcineurin inhibitors, and mammalian target of rapamycin (mTOR) inhibitors [ 6 ]. Sarcopenia also had significant impacts on the development of diabetes mellitus, the risk of infection, the length of hospitalization, and mortality in patients who underwent liver transplantation [ 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ].…”
Section: Sarcopenia In Chronic Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The degree of sarcopenia was associated with Child-Pugh score in patients with cirrhosis, and sarcopenia was a predictor of survival independently or in combination with the model for end-stage liver disease (MELD) score, especially in patients with low scores (<15) [ 109 , 111 , 114 ]. Unfortunately, after liver transplantation, sarcopenia did not improve and even worsened because of immunosuppressive drugs such as steroids, calcineurin inhibitors, and mammalian target of rapamycin (mTOR) inhibitors [ 6 ]. Sarcopenia also had significant impacts on the development of diabetes mellitus, the risk of infection, the length of hospitalization, and mortality in patients who underwent liver transplantation [ 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ].…”
Section: Sarcopenia In Chronic Liver Diseasementioning
confidence: 99%
“…The presence of osteoporosis in patients with liver disease adversely affects their clinical outcomes in terms of quality of life, survival, and liver-related complications, regardless of etiology and severity [ 1 , 2 ]. Since sarcopenia was first proposed as the concept of age-related loss of muscle mass in 1989, numerous studies have demonstrated its molecular pathogenesis and clinical implications, especially in the context of chronic liver disease, as the liver is an important organ for carbohydrate, protein, and lipid metabolism, whose deterioration results in protein supply dysregulation and hyperammonemia, inevitably influencing skeletal muscle homeostasis [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Therefore, sarcopenia was observed almost half of patients with liver cirrhosis, and negatively influenced the mortality and prognosis of liver disease [ 3 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enterocytes also converts glutamine to glutamate and ammonia through the activity of glutaminase. Normally, ammonia is detoxified in the liver by conversion to urea in the urea cycle [ 16 ]. Ammonia is also consumed in the conversion of glutamate to glutamine, a reaction that depends on the activity of glutamine synthetase.…”
Section: Mechanism Of Sarcopenia In Liver Cirrhosismentioning
confidence: 99%
“…As muscle tissue contributes to the removal of circulating ammonia by increasing glutamine synthesis, sarcopenia is not only associated with worsening of clinical conditions and increased mortality in cirrhotic patients[139] but also represents an independent risk factor for HE[25,140,141]. Adequate protein intake is therefore extremely important in cirrhotic patients with HE[142], both in terms of timing and quality of nutrient ingestion.…”
Section: Dietary Approachmentioning
confidence: 99%